ABHYANGA IN NEW BORN BABY AND NEONATAL MASSAGE - A REVIEW - Raskar, Swapnil; S, Rajagopala (International Journal of Ayurveda and Pharma Research, 2015)
Neonatal period is very crucial phase of life. One has to provide systematic, luxurious and sophisticated neonatal care. Ayurveda mentioned very scientific approach toward newborn care as Jatamatra Paricharya; means a protocol. Abhyanga is one of these care protocols. Neonatal massage with lubricant is in practice around the world and resembles with Ayurveda Abhyanga process. In vitally stable neonates Abhyanga can be done with particular precaution considering the indications and contraindications. Abhyanga and massage are not totally identical. Abhyanga increases the strength, nourishes body, improves skin texture and accelerates the healthy growth and development of newborn. Increased weight gain, reduced pain, enhanced attentiveness, reduced depression and enhanced immune function (increased natural killer cells and natural killer cell activity) are some advantages of newborn massage. During Abhyanga prevent harmful and painful practices and social taboos, like stretching of limbs, pulling of ear and nasal cartilages etc should not be practiced. Oil which is suitable for baby according to local conditions should be use. Bala Taila is one of the best oil among the all oil preparations in Ayurveda. Hence though Abhyanga is consider as complimentary and traditional ancient practice, it is very useful for the healthy newborn and contribution to modern health society. The present article is a systematic review of the neonatal massage across the world to establish the role of Ayurveda newborn care protocols having potential to contribute neonatal health, as key message to modern health world.